THE EXTENT OF THE NEUROCOGNITIVE IMPAIRMENT ASSOCIATED WITH CHRONIC PAIN ON THE NEUROPSYCHOLOGICAL TEST PERFORMANCE; META-ANALYSIS AND LITERATURE REVIEW - Rehman, Yasir (My University, 2014)
Introduction: Cognitive complaints are often reported by patients who also describe chronic pain. Reviews suggest chronic pain is likely to be associated with weaknesses, relative to control groups, in at least some cognitive functions including processing speed, attention, and possibly working memory, but differences between studies obscure the size of effects. Objective: This study provided a quantitative analysis of the magnitude of the association between chronic pain and neurocognitive test performances. Brief literature review is also done to focus on the functional brain changes associated with the chronic pain. Methods: Meta-analysis was performed using the Cochrane, PRISMA guidelines. The analysis included published experimental design and the tests were studied at least 3 times, by different researchers, and the outcomes were combined within the same cognitive test. Tests were excluded when heterogeneity of variance exceeded I2 = 0.60. Pain subgroups were combined. Results: 23 studies met criteria and involved heterogeneous pain populations, or subgroups including back pain, whiplash, and fibromyalgia. Seven tests had sufficient variance homogeneity. Effects sizes (- ve = chronic pain relative weakness) were: Tests measuring the attention such as PASAT and TEA, working memory (WAIS- digit span), executive functions such as Stroop test, TMT showed significant weaker performance on the tests performance, whereas performance on the test of visuospatial abilities such as ROCF and Corsi block test and WCST test, did not showed significant association. Conclusions: Chronic pain was associated with statistically significant performance reductions. The pattern suggests that chronic pain is associated with poorer performance in at least some tasks requiring processing speed, attention, working memory and learning. Differences between pain and control groups ranged from about 1/3 standard deviation to just under a full standard deviation. Too little research is available on non-verbal memory and executive functions in chronic pain.
COGNITIVE IMPAIRMENT ASSOCIATED WTH CHRONIC PAIN
Keywords: Chronic pain; Neurospychological Test Performance; cognitive deficits; Fibromyalgia; Whiplash; Meta-analysis